Medical-surgical nursing : patient-centered collaborative care - Winkelman, Chris; Ignatavicius, Donna D.; Workman, M. Linda (Elsevier, 2013)
The Clinical Companion for Ignatavicius & Workman: Medical-Surgical Nursing: Patient-Centered Collaborative Care, 7th Edition, is an easy-to-use, A-Z guide to 245 common medical-surgical conditions and their management. Written in a reader-friendly, direct-address style, this handbook is a convenient quick reference that you can carry with you on clinical days.